Physiological characteristics, evaluation and prescription of aerobic training in futsal Características fisiológicas, avaliação e prescrição do treinamento aeróbio no futsal - Arins F.B. (2015)
© 2015, Universidade Federal de Santa Catarina. All right reserved.Futsal has intermittent characteristics with different requirements of displacements and changes of direction, requiring simultaneously aerobic and anaerobic capacities of athletes. So, during counter-attacks and returns to defense or fast movements to get rid or perform marking, there is maximum mobilization of specific capabilities of the sport and the ability to perform high-intensity intermittent exercise is a key factor of performance. The aim of this study was to perform an expositive review on the physiological characteristics, high-intensity interval training and aerobic evaluation methods that have been used and suggested in scientific literature in original studies. A search in scientific portals Google Scholar, Scopus®, SciELO®, ScienceDirect® (Elsevier) and PubMed® was conducted to find articles with publication date since 2000 using the following terms in different combinations: “Futsal”, “performance”, “aerobic evaluation”, “high-intensity interval training”, “field tests” and their variations in English. Analysis of physiological indexes related to game performance can help in the knowledge about the aerobic fitness of Futsal players and improve training assessment, prescription and monitoring, also serving as a reference to assist professionals of this sport in the preparation of high intensity interval training programs to meet the particular needs of the sport. Field tests with specific features of the sport were created as a means of assessment and also training prescription and are recommended due to their specificity and ecological validity.